2017
DOI: 10.1038/s41598-017-09172-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing spring temperatures favor oak seed production in temperate areas

Abstract: The changes in reproductive phenology (i.e. timing of flowering and fruiting) observed in recent decades demonstrate that tree reproduction has already been altered by climate change. However, understanding the impact of these changes in reproductive success and fitness remains a major challenge for ecologists. We describe here a previously unreported phenomenon: a significant increase in the reproductive effort (seed production) of temperate oaks with increasing spring temperature, observed over the last deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 56 publications
(61 reference statements)
4
59
0
5
Order By: Relevance
“…Previous studies have suggested that pollen synchrony (i.e. the duration of the seasonal spreading of airborne pollen) could be one of the main drivers of oak masting Pesendorfer et al 2016;Bogdziewicz et al 2017b) because high spring temperatures are known for their synchronising effect on leaf budburstleaf phenology providing a proxy of pollen phenology (Koenig et al 2012)and are also favourable to high fruiting (Pearse et al 2014;Caignard et al 2017;Nussbaumer et al 2018). Our results show that pollen synchrony is not correlated to the annual airborne pollen amount (Fig.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Previous studies have suggested that pollen synchrony (i.e. the duration of the seasonal spreading of airborne pollen) could be one of the main drivers of oak masting Pesendorfer et al 2016;Bogdziewicz et al 2017b) because high spring temperatures are known for their synchronising effect on leaf budburstleaf phenology providing a proxy of pollen phenology (Koenig et al 2012)and are also favourable to high fruiting (Pearse et al 2014;Caignard et al 2017;Nussbaumer et al 2018). Our results show that pollen synchrony is not correlated to the annual airborne pollen amount (Fig.…”
Section: Discussionmentioning
confidence: 42%
“…In line with the last hypothesis, several empirical studies have shown that daily airborne pollen amounts strongly depends on weather conditions during pollen release and aerial diffusion for many plant species (Garc ıa-Mozo et al 2012;Grewling et al 2014;Kasprzyk et al 2014;Fuhrmann et al 2016;Sabit et al 2016). Likewise, spring weather are related to fruiting intensity in some masting species (Garc ıa-Mozo et al 2012;Pearse et al 2014;Fern andez-Mart ınez et al 2015;Koenig et al 2015;Bogdziewicz et al 2017a;Caignard et al 2017;Nussbaumer et al 2018), which suggests that unfavourable weather conditions for pollen release, aerial diffusion or synchronised flowering may cause pollen limitation (Koenig et al 2012Bogdziewicz et al 2017b).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, global warming is predicted to increase wind speed (IPCC, ), which suggests a decrease in dispersal limitation during succession. Increasing CO 2 (Hikosaka, Kinugasa, Oikawa, Onoda, & Hirose, ) and warming (Caignard et al, ) influence the quantity and quality of seeds. Warming lends a competitive advantage to vascular plants over lichens in Arctic tundra (Cornelissen et al, ), and seed germination rate increases with temperature (Graae et al, ).…”
Section: Dispersal Primary Succession and Climate Changementioning
confidence: 99%
“…and the other two (Gedre-Bas and Gabas) at ∼1200 m a.s.l. The sampling date was chosen as close as possible to the fruiting peak at both elevations (see Caignard et al , 2017 for a complete description of the sampling sites and fruiting phenology). In each site, acorns were collected from three trees randomly selected among the dominant adults.…”
Section: Methodsmentioning
confidence: 99%